2015
DOI: 10.2134/agronj14.0355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Management Factor Contributions to Reduce Corn Yield Gaps

Abstract: ABSTRACTe need to intensify agricultural production due to a growing human population requires yield gaps to be closed. In 2009 and 2010, ve management factors were assessed for their individual and cumulative contributions to reducing the corn (Zea mays L.) yield gap and yield components in a corn-soybean [Glycine max (L.) Merr.] rotation. Five management factors (plant population, transgenic insect resistance, fungicide containing strobilurin, P-S-Zn fertility, and N fertility) were evaluated. An incomplete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 51 publications
4
46
1
5
Order By: Relevance
“…The yield response of hybrids, averaged across environments, to high N fertilizer (252 kg N ha ‐1 ) ranged from +4.47 to +5.64 Mg ha ‐1 and the yield response to increased plant density ranged from ‐0.60 to +0.58 Mg ha ‐1 . Compared with results from previous studies under similar agronomic conditions, the findings reported here identified substantially greater yield ranges for both response to high N fertilizer (Haegele et al, 2013) and increased plant density (Ruffo et al, 2015), demonstrating greater genetic variability for these traits in current elite maize hybrids. Moreover, four groups of hybrids were identified: group 1B included 25% of the hybrids with below‐average yield response to high N but above‐average response to increased plant density; group 2B included 24% of the hybrids with above‐average yield responses to both high N and increased plant density; group 3B contained 25% of the hybrids with below‐average yield response to both high N and plant density; and group 4B consisted of 26% of the hybrids with above‐average yield response to high N but below‐average response to increased plant density.…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…The yield response of hybrids, averaged across environments, to high N fertilizer (252 kg N ha ‐1 ) ranged from +4.47 to +5.64 Mg ha ‐1 and the yield response to increased plant density ranged from ‐0.60 to +0.58 Mg ha ‐1 . Compared with results from previous studies under similar agronomic conditions, the findings reported here identified substantially greater yield ranges for both response to high N fertilizer (Haegele et al, 2013) and increased plant density (Ruffo et al, 2015), demonstrating greater genetic variability for these traits in current elite maize hybrids. Moreover, four groups of hybrids were identified: group 1B included 25% of the hybrids with below‐average yield response to high N but above‐average response to increased plant density; group 2B included 24% of the hybrids with above‐average yield responses to both high N and increased plant density; group 3B contained 25% of the hybrids with below‐average yield response to both high N and plant density; and group 4B consisted of 26% of the hybrids with above‐average yield response to high N but below‐average response to increased plant density.…”
Section: Resultscontrasting
confidence: 60%
“…In addition, continued increases in maize yield will depend on a hybrid's ability to utilize resources more efficiently when grown under greater plant densities (Tollenaar and Lee, 2002) and under favorable agronomic conditions (Boomsma et al, 2009). Nonetheless, increased plant density needs to be in synergy with other intensified management factors, such as better soil fertility, to minimize the current maize yield gap that exists in the U.S. Corn Belt (Ruffo et al, 2015).…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, water deficits during reproductive stages impact soybean yield more than deficits during vegetative ones (Ashley & Ethridge, ; Brown, Caviness, & Brown, ; Doss, Pearson, & Rogers, ). Variations in seed number and individual seed weight are used to understand the timing and mechanisms behind yield differences to different stress levels and crop managements (Board & Tan, ; Ruffo, Gentry, Henninger, Seebauer, & Below, ).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in seed number and individual seed weight are used to understand the timing and mechanisms behind yield differences to different stress levels and crop managements (Board & Tan, 1995;Ruffo, Gentry, Henninger, Seebauer, & Below, 2015).…”
mentioning
confidence: 99%